1987
DOI: 10.1111/j.1463-6409.1987.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

The tubicolous habit amongst the Tanaidacea (Crustacea, Peracarida) with particular reference to deep‐sea species

Abstract: Although tanaids are thought of as a largely tubicolous order of peracarids, relatively few species have in fact been recorded from tubes. However, many species of the genus Typhlotanais recently collected from deep‐sea sediments are tubicolous and attach or incorporate a wide range of materials to a mucous tube formed of secretions from glands within the pereonal cavity. These include mud particles, sand grains, sponge spicules and foraminiferan tests. Silica and calcium usually form the dominant ions in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 31 publications
(28 reference statements)
0
20
0
Order By: Relevance
“…Species like Nototanais antarcticus live in the aggregations of tangled corridors, while typhlotanaids are known as tube-dwellers (Hassack and Holdich 1987;Blazewicz-Paszkowycz 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Species like Nototanais antarcticus live in the aggregations of tangled corridors, while typhlotanaids are known as tube-dwellers (Hassack and Holdich 1987;Blazewicz-Paszkowycz 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Hassack & Holdich (1987) have commented upon the fact that colonies of tubicolous tanaids can attain very high population densities, and have pointed out the protective role of tubes against predators, as also during reproduction and moulting. That similar closely-packed colonies characterize both epifaunal and infaunal corophioid populations (Connell 1963 ;Thorson 1971 ;Moore 1985) reflects the fact that, as in sessile colonial taxa, particulate food in abundance -in the form of seston or depositing particles -is brought to their vicinity, and continually replenished, by external agencies.…”
Section: (E) Phylogenetic Implications Of Differences In Feeding Behamentioning
confidence: 99%
“…Passive dispersal by marine currents or rafting can be invoked as the potential responsible mechanisms (Bamber 2012;Bamber and Błażewicz-Paszkowycz 2013). Tanaidaceans usually live in selfconstructed tubes (Johnson and Attramadal 1982;Hassack and Holdich 1987); alternatively, they burrow in the sediment, although some are associated with algal mats (Edgar 2012), mangroves or sunken wood (Larsen et al 2013;Błażewicz-Paszkowycz et al 2014). The tanaidacean specimens found in this study were far too small to be directly observed in their microhabitats, but since some of them were numerous in corral rubble samples, they may be inferred-similarly to many other invertebrates (Plaisance et al 2011)-to inhabit crevices, fissures, and cracks in scleractinian skeletons.…”
Section: Discussionmentioning
confidence: 99%